Studi Kasus Yayasan X: Hubungan antara Hasil Tes Seleksi Karyawan Baru dengan Hasil Kinerja Karyawan Setelah Bekerja Min. 12 Bulan - Bernadetta Junita Santosa (Bina Nusantara University, 2010)
Case study in Institution X is purposed to see connection between new employee selection result as psychological test and employee interview in KPI, a competencies and total score after working at least 1 year. This case study related to how important the connection between the two variables, especially related to validity from existing selection test. This research uses quantitative method (statistical calculation) with gathering main data in Institution X, with descriptive and correlation method. Subjects are 160 employees selected on 2008 and have been through performance evaluation on 2009, in different positions and levels. The general result shows that there is no significant connection between test result and employees’ performance result in KPI, competencies and total score. Suggestion for this study is by giving test tools renovation for selecting new employees.